My Journey at the Nuclear Brink - Ms. Hajira Asaf Khan (CISS Insight Journal, 2016)
My Journey at the Nuclear Brink is the memoirs of William J. Perry, a former serviceman of the United States Air Force, a mathematician, and an entrepreneur of defence and reconnaissance technologies. The author served as Undersecretary of Defence to Harold Brown, in the Carter Administration, as Secretary of Defence in the Clinton Administration and had previously served in the capacity of consultant with the Kennedy Administration, most notably, during the Cuban Missile Crisis.William J. Perry has been a vocal advocate of arms control and disarmament from the very beginning of his political career. According to him, being stationed in Tokyo after the Second World War had ended, and seeing the destruction that the city had suffered from US fire-bombings left a lasting effect on him. The subsequent realization that similar destruction could now be caused by using just one nuclear bomb, developed in him the conviction that all efforts must be made to avoid the use of these weapons in future.In his days serving as Undersecretary of Defence, he was responsible for the development of the “system of systems” which included stealth technology, smart sensors and smart weaponry, a signature development in America’s defence technology during the 70s and 80s. The importance of this work was realized later in Operation Desert Storm when it was put to use, especially stealth aircraft. Perry’s account maintains that the offset strategy of the times was the reason that Soviet superiority was met with technological advancement thus, making the possibility of a nuclear strike less likely.